2016
DOI: 10.1111/dom.12606
|View full text |Cite
|
Sign up to set email alerts
|

One‐year metreleptin improves insulin secretion in patients with diabetes linked to genetic lipodystrophic syndromes

Abstract: Recombinant methionyl human leptin (metreleptin) therapy was shown to improve hyperglycaemia, dyslipidaemia and insulin sensitivity in patients with lipodystrophic syndromes, but its effects on insulin secretion remain controversial. We used dynamic intravenous (i.v.) clamp procedures to measure insulin secretion, adjusted to insulin sensitivity, at baseline and after 1 year of metreleptin therapy, in 16 consecutive patients with lipodystrophy, diabetes and leptin deficiency. Patients, with a mean [± standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 22 publications
0
33
0
4
Order By: Relevance
“…In patients with lipodystrophy, metreleptin therapy ameliorates metabolic abnormalities by reducing food intake (3,12,13), improving insulin resistance and diabetes (4,(13)(14)(15), and reducing ectopic lipid (7). These improvements in glucose and lipid metabolism are likely due in part to the reduction in food intake, but the clinical effects of metreleptin that are independent of changes in food intake have been poorly explored in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with lipodystrophy, metreleptin therapy ameliorates metabolic abnormalities by reducing food intake (3,12,13), improving insulin resistance and diabetes (4,(13)(14)(15), and reducing ectopic lipid (7). These improvements in glucose and lipid metabolism are likely due in part to the reduction in food intake, but the clinical effects of metreleptin that are independent of changes in food intake have been poorly explored in humans.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, leptin increases energy expenditure and reduces food intake [25]. Furthermore, physiological increase in plasma leptin level has been shown to increase insulin secretion [26]. Adiponectin increases glucose uptake in muscles and insulin sensitivity, suppresses gluconeogenesis in hepatocytes and increases β-oxidation [27].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, metreleptin reduced hypertriglyceridemia and improved glycemia in severely hypoleptinemic patients with partial lipodystrophy and severe metabolic derangements (baseline HbA1c >8%, triglycerides >500 mg/dL, leptin <4 ng/mL) (46). In a second study, metreleptin improved triglycerides and indices of insulin sensitivity and secretion in FPLD2 patients with moderate to severe hypoleptinemia (56). However, in a third study, no glycemic improvement was observed in FPLD2 patients with serum leptin <7 ng/mL (57).…”
Section: Treatment Of Lipodystrophy Syndromesmentioning
confidence: 99%